Impact of age on reperfusion success and long-term prognosis in ST-segment elevation myocardial infarction – A cardiac magnetic resonance imaging study. (April 2021) - Gabriel Topal, Divan; Aleksov Ahtarovski, Kiril; Lønborg, Jacob; Høfsten, Dan; Nepper-Christensen, Lars; Kyhl, Kasper; Schoos, Mikkel; Ghotbi, Adam Ali; Göransson, Christoffer; Bertelsen, Litten; Holmvang, Lene; Helqvist, Steffen; et al.
Abstract: Background: Coronary collateral circulation and conditioning from remote ischemic coronary territories may protect culprit myocardium in the elderly, and younger STEMI patients could suffer from larger infarcts. We evaluated the impact of age on myocardial salvage and long-term prognosis in a contemporary STEMI cohort. Methods: Of 1603 included STEMI patients 807 underwent cardiac magnetic resonance. To assess the impact of age on infarct size and left ventricular ejection fraction (LVEF) as well as the composite endpoint of death and re-hospitalization for heart failure we stratified the patients by an age cut-off of 60 years. Results: Younger STEMI patients had smaller final infarcts (10% vs. 12%, P = 0.012) and higher final LVEF (60% vs. 58%, P = 0.042). After adjusting for multiple potential confounders age did not remain significantly associated with infarct size and LVEF. During 4-year follow-up, the composite endpoint occurred less often in the young (3.2% vs. 17.2%; P < 0.001) with a univariate hazard ratio of 5.77 (95% CI, 3.75–8.89; p < 0.001). Event estimates of 4 subgroups (young vs. elderly and infarct size beyond vs. below median) showed a gradual increase in the occurrence of the composite endpoint depending on both age and acute infarct size (log-rank p < 0.001). Conclusion: Having a STEMI after entering the seventh decade of life more than quadrupled the risk of future death or re-hospitalization for heart failure. Risk of death and re-hospitalization depended on both advanced age and infarct size, albeit no substantial difference was found in infarct size, LVEF and salvage potential between younger and elderly patients with STEMI.